Efficacy of antimicrobial plant crude extracts on the growth in Colletotrichum gloeosporiodes f. sp. manihotis - Fokunang, C.N.; Akem, C.N.; Ikotun, T.; Dixon, Alfred G.O. (2000)
This study was conducted to investigate a cheap and readily available alternative control measure for cassava anthracnose disease causal agent (Colletotrichum gloeosporioides f. sp. manihotis), through the use of antimicrobial crude plant extracts such as neem (Azadirachta indica), bitter leaf (Vernonia amygdalina), Ocimum gratissimum and Xylopia aethiopica, on the fungal growth parameters (mycelial growth, sporulation and germ tube development). The extracts at concentration levels of 25, 50, 75 and 100% full strength concentration showed an inhibitory effect on mycelial growth, germ tube development and sporulation of fungal isolates 05FCN, 10FCN, 12FCN and 26FCN. Neem seed and leaf extracts at 100% showed a total reduction in sporulation in most of the fungal isolates. The inhibitory properties of the plant crude extracts indicated a promising control option for consideration in cassava treatments of planting stocks, particularly in areas where farming is at a basic subsistent level, and less available money to meet the high cost of pesticides.